First Ukrainian experience using noninvasive expandable modular endoprosthesis for the treatment of patients with malignant tumors of long bones - Vyrva, Oleg; Malyk, Roman (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
First Ukrainian experience using noninvasive modular expandable endoprosthesis in patients with malignant bone tumors. Introduction. The article focused on the surgical treatment of patients with malignant bone tumors by expandable endoprosthesis. Purpose. To present stage of development and the main features using of expandable endoprostheses in malignant bone tumors surgery in patients with incomplete skeletal growth. Materials and methods. Data of 6 children with bone defects of distal femur (5) and proximal tibia (1) following treatment of malignant bone tumors which were implanted noninvasive expandable endoprosthesis. Results. The analysis of the evolution of the expandable endoprosthesis was presented; advantages and disadvantages of modern systems for tumor arthroplasty in children were present also. The experience of using MUTARS Xpand system was presented on clinical examples in patients with malignant bone tumors with incomplete skeletal growth. Conclusion. Direction tumor expandable prosthesis designs is still evolving, but it is the best method to prevent limbs discrepancy and to achieve excellent functional results in childhood patients with malignant tumors of long bones.